Гужем лымы: Повесть / Генрих Перевощиков - Перевощиков Генрих Ксенофонтович (Удмуртия, 1984)
Экземпляры: ф.3 (20170828) / Инвентарный номер: 015414 / Цена: 1.00 / Авт.знак: П 27 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Удм)6